非圆齿轮传动弯曲强度计算方法研究 - 李纪强; 刘忠明 (Jixie chuandong)
According to the machining principle,the tooth profile mathematical model of non-circular gear is established,and differences of the tooth profile are compared between the non-circular gear and its equivalent cylindrical gear.On this basis,the feasibility is studied for using the method of cylindrical gear bending stress to calculate the non-circular gear bending stress.The effect of pressure angle,contact ratio and other geometry and meshing characteristics are analyzed.Last,a reasonable calculation method of non-circular gear bending stress is proposed,and its correctness is proved with the finite element method.